Tumor margins that lead to reoperation in breast cancer: A retrospective register study of 4,489 patients - Lepomäki Maiju; Karhunen-Enckell Ulla; Tuominen Jalmari; Kronqvist Pauliina; Oksala Niku; Murtola Teemu; Roine Antti (WILEY, 2022)
Background and Objectives
Optimal margins for ductal carcinoma in situ (DCIS) remain controversial in breast-conserving surgery (BCS) and mastectomy. We examine the association of positive margins, reoperations, DCIS and age.
Methods
A retrospective study of histopathological reports (4489 patients). Margin positivity was defined as ink on tumor for invasive carcinoma. For DCIS, we applied 2 mm anterior and side margin thresholds, and ink on tumor in the posterior margin.
Results
The incidence of positive side margins was 20% in BCS and 5% in mastectomies (p < 0.001). Of these patients, 68% and 14% underwent a reoperation (p < 0.001). After a positive side margin in BCS, the reoperation rates according to age groups were 74% (<49), 69% (50-64), 68% (65-79), and 42% (80+) (p = 0.013). Of BCS patients with invasive carcinoma in the side margin, 73% were reoperated on. A reoperation was performed in 70% of patients with a close (<= 1 mm) DCIS side margin, compared to 43% with a wider (1.1-2 mm) margin (p = 0.002). The reoperation rates were 55% in invasive carcinoma with close DCIS, 66% in close extensive intraductal component (EIC), and 83% in close pure DCIS (p < 0.001).
Conclusions
Individual assessment as opposed to rigid adherence to guidelines was used in the decision on reoperation.